TreeMap, a tree-level model of conterminous US forests circa 2014 produced by imputation of FIA plot data - Karin L. Riley (Nature Portfolio, 2021)
Measurement(s) forested area Technology Type(s) machine learning Factor Type(s) biophysical variables • geographic location • forest type • forest height • forest percent cover Sample Characteristic - Environment vegetation layer Sample Characteristic - Location United States of America Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13285904